Using Music As a Training Tool-Instructional Systems Development - Millbower, Lenn (Association for Talent Development, 2004)
Music is present in almost every facet of human life. So why doesn't it show up in training? Throughout time people have used music to learn their ABCs as well as more complex societal histories and even scientific formulas. Could you, the trainer, be missing out on a useful tool that can: establish a positive mood minimize negative conditions aid memorization enhance reviews foster creativity? This Infoline shows you how to put music to effective use in training. It explains its effect on the human brain and how to harness those effects at will. You'll also learn to select the right kind of music for any training activity as well as avoid any problems that using music might cause. So why not tap into the power of music today?